2020
DOI: 10.3390/rs12091513
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Stem Volume in Eucalyptus Plantations Using Airborne LiDAR: A Comparison of Area- and Individual Tree-Based Approaches

Abstract: Forest plantations are globally important for the economy and are significant for carbon sequestration. Properly managing plantations requires accurate information about stand timber stocks. In this study, we used the area (ABA) and individual tree (ITD) based approaches for estimating stem volume in fast-growing Eucalyptus spp forest plantations. Herein, we propose a new method to improve individual tree detection (ITD) in dense canopy homogeneous forests and assess the effects of stand age, slope and scan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 70 publications
0
21
0
3
Order By: Relevance
“…This constitutes an outstanding result when compared to other studies involving the tree individualization approach [74] and serves as an example of improvements to lidar-based forest inventory. This relatively new paradigm is therefore perfect for tree-level attribute estimation in Eucalyptus plantations where such in-depth detail is necessary for accommodating small-scale variations that are untraceable via plot-based estimation procedures [21,[75][76][77][78][79]. Herein, the lidar-derived crown-metrics were found to provide a satisfactory estimation of Ht, dbh, and AGC, and the best results were obtained while employing a LME with SID as the random-effect variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This constitutes an outstanding result when compared to other studies involving the tree individualization approach [74] and serves as an example of improvements to lidar-based forest inventory. This relatively new paradigm is therefore perfect for tree-level attribute estimation in Eucalyptus plantations where such in-depth detail is necessary for accommodating small-scale variations that are untraceable via plot-based estimation procedures [21,[75][76][77][78][79]. Herein, the lidar-derived crown-metrics were found to provide a satisfactory estimation of Ht, dbh, and AGC, and the best results were obtained while employing a LME with SID as the random-effect variable.…”
Section: Discussionmentioning
confidence: 99%
“…Trees in the given Eucalyptus stand were found to be quite similar, which was evident from the low values of GC (<0.33) and the close proximity of Lorenz curves to the perfect equality line in Figure 8. The differences found in younger stands may be related to errors associated with tree detection and crown delineation at this age, which is commonly the main source of errors in tree-level approaches [79,89]. Further research may clarify the relationships between the theoretical threshold GC < 0.33 [72] and productivity loss in Eucalyptus plantations.…”
Section: Discussionmentioning
confidence: 99%
“…Among some studies, it was found that the spatial resolution has a key role in the accuracy of the biomass. The spatial resolution of Landsat can achieve a low accuracy [112], while the SPOT satellites [113], GeoEye [114], and Quickbird [55] can achieve medium to high accuracy, WorldView [115] and spatial resolution of LiDAR can achieve high accuracy [116]. Overall, the more accurate the modeling, the greater the approximation to the observed values [117].…”
Section: Biomass Estimationmentioning
confidence: 99%
“…Among these, only one paper exclusively uses passive RS data [21], while 29 papers use at least one LiDAR dataset in the analysis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30]. Ten papers exclusively use airborne laser scanning (ALS) data [4,6,7,10,11,13,18,23,26,27], nine papers exclusively use terrestrial laser scanning (TLS) data in the analysis [3,9,15,16,20,22,24,25,30], two papers exclusively use mobile laser scanning (MLS) data …”
mentioning
confidence: 99%
“…Finally, five papers use combined active and passive remote sensing data sets [2,14,17,19,28]. Regarding the scale of the analysis, 18 of the studies perform individual tree level (ITL) analysis [1][2][3][8][9][10][11][12][14][15][16]19,20,[23][24][25][26]30], eight papers report stand level (SL) analysis [6,7,17,18,21,22,27,29] and four report a combination of ITL and SL [4,5,13,28]. Tree position, diameter at breast height (DBH) and individual tree height (h) are the most common variables of interest, analyzed in nine, six and six papers, respectively, while the most commonly used methods are 3D reconstruction, point filtering and statistical modelling, which are used in eight, five and five papers, respectively (see Table 1).…”
mentioning
confidence: 99%